The Role of Family Support in Shaping Girls’ Self-Confidence: A Literature Review - Bun Pichchenda; Marites Geronimo; Suzette DC Domingo (WISE Pendidikan Indonesia, 2025)
This study aims to explore the role of family support in shaping girls’ self-confidence by synthesizing findings from recent empirical and conceptual studies published between 2018 and 2025. Using a literature review approach, this research integrates evidence from ten peer-reviewed articles indexed in Scopus, Web of Science, and nationally accredited journals (SINTA 1/2) to identify patterns, determinants, and cultural variations influencing girls’ psychological development. The results reveal that family support manifested through emotional warmth, open communication, and democratic parenting serves as the primary determinant of girls’ self-confidence. Authoritative and empathetic parenting styles are consistently associated with higher levels of self-efficacy, emotional regulation, and social assertiveness, whereas overprotection and authoritarian control are linked to self-doubt and limited autonomy. Socioeconomic background and parental education also indirectly affect confidence development by shaping communication quality and emotional availability. Furthermore, cultural and gender norms influence how girls internalize confidence and self-worth within different social contexts. The discussion highlights that family support operates as both a psychological and sociocultural mechanism that fosters competence, agency, and empowerment among young women. The findings underscore the necessity for gender-sensitive family education programs that promote empathy, emotional literacy, and autonomy to enhance girls’ confidence and long-term well-being. The implications of this research emphasize the integration of family-based interventions into educational and community frameworks to strengthen the foundations of girls’ psychological empowerment.